2009
DOI: 10.1590/s1516-14392009000400018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of carburization time and temperature on the mechanical properties of carburized mild steel, using activated carbon as carburizer

Abstract: Due to the complexity of controlling parameters in carburization, there has been relatively little work on process variables during the surface hardening process. This work focuses on the effects of the carburizing temperature and time on the mechanical properties of mild steel carburized with activated carbon, at 850, 900 and 950 °C, soaked at the carburizing temperature for 15 and 30 minutes, quenched in oil, tempered at 550 °C and held for 60 minutes. Prior carburization process, standard test samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 7 publications
(6 reference statements)
1
25
1
3
Order By: Relevance
“…Cooling rate influenced the stability of C-Cr associate. The mechanical property of CLAM steel subjected to different heat treatment [6].…”
Section: Resultsmentioning
confidence: 99%
“…Cooling rate influenced the stability of C-Cr associate. The mechanical property of CLAM steel subjected to different heat treatment [6].…”
Section: Resultsmentioning
confidence: 99%
“…(4) The effective case depth governed by carburization temperature, time, the carbon content of steel, and the carbon potential of atmosphere is calculated, and a simple and practical set of guidelines for optimizing gas carburization has been provided for plant production. Aramide et al (5) studied the effects of the carburization temperature and time on the mechanical properties of mild steels carburized with activated carbon, and observed that the mechanical properties of mild steels were strongly affected by the process of carburization, carburization temperature, and soaking time at the carburization temperature. They concluded that the optimum combination of mechanical properties is achieved at the carburization temperature of 900 ℃ followed by oil quenching and tempering at 550 ℃.…”
Section: Introductionmentioning
confidence: 99%
“…The hardness and elastic modulus at each point on and inside the gear surface are different after carburization, such that a carburized gear can be regarded as a heterogeneous material [8,9]. Thus, the strengths and shear stresses at different ECDs are nonlinear in gear meshing.…”
Section: Introductionmentioning
confidence: 99%